Voices from Shanghai : Jewish exiles in wartime China - Eber, Irene, 1929-2019 (University of Chicago Press, 2008)
When Hitler came to power and the German army began to sweep through Europe, almost 20,000 Jewish refugees fled to Shanghai. A remarkable collection of the letters, diary entries, poems, and short stories composed by these refugees in the years after they landed in China, Voices from Shanghai fills a gap in our historical understanding of what happened to so many Jews who were forced to board the first ship bound for anywhere. Once they arrived, the refugees learned to navigate the various languages, belief systems, and ethnic traditions they encountered in an already booming intern.